2014
DOI: 10.1093/schbul/sbu116
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Activity and the "Stream of Consciousness" in Schizophrenia--Neurophenomenal Hypotheses

Abstract: Schizophrenia is a multifaceted disorder with various symptoms including auditory hallucinations, egodisturbances, passivity phenomena, and delusions. Recent neurobiological approaches have focused on, especially, the abnormal contents of consciousness, the "substantive parts" as James said, to associate them with the neural mechanisms related to sensory, motor, and cognitive functions, and the brain's underlying stimulus-induced or task-evoked activity. This leaves open, however, the neural mechanisms that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 59 publications
(69 reference statements)
1
36
0
Order By: Relevance
“…''Inner time consciousness'' has, however, also described in the phenomenological tradition of philosophy by Edmund Husserl by other phenomenal features as for instance protention, primal presentation, and retention (see Fuchs, 2013;Northoff, 2014a) for an overview in the context of schizophrenia). While these phenomenal features may be well compatible or, even stronger, imply or entail ''sensible continuity'' and ''continuous change'' that relationship needs to be demonstrated on both empirical, e.g., neural, and phenomenal, e.g., conceptual, levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…''Inner time consciousness'' has, however, also described in the phenomenological tradition of philosophy by Edmund Husserl by other phenomenal features as for instance protention, primal presentation, and retention (see Fuchs, 2013;Northoff, 2014a) for an overview in the context of schizophrenia). While these phenomenal features may be well compatible or, even stronger, imply or entail ''sensible continuity'' and ''continuous change'' that relationship needs to be demonstrated on both empirical, e.g., neural, and phenomenal, e.g., conceptual, levels.…”
Section: Resultsmentioning
confidence: 99%
“…This will contribute to better understanding of the neurophenomenal relationships of the ''stream of consciousness'' in ''inner time consciousness'' in particular and consciousness in general. Moreover, our neuro-phenomenal balance hypothesis may open a door to better understanding many symptoms in psychiatric disorders like depression or schizophrenia that may ultimately be traced to temporal abnormalities in 'inner time consciousness' (see Fuchs, 2013;Northoff, 2014aNorthoff, , 2014b. That, in turn, may make possible the development of novel diagnostic and eventually also therapeutic markers in these disorders.…”
Section: Resultsmentioning
confidence: 99%
“…27,32,51,52 A meta-analysis found that externally guided (goal-oriented) decision-making tasks yielded stronger activity changes in lateral frontal and parietal regions of the brain (associated with the CEN), whereas internally guided tasks yielded increased activity in the DMN, including the pregenual anterior cingulate cortex, ventromedial prefrontal cortex, dorsomedial prefrontal cortex, posterior cingulate cortex, and precuneus 53 (also see Nakao et al 38 and Northoff 54 ). Additionally, comparing brain activity while counting heartbeats (endogenous) compared with counting auditory tones (exogenous), Wiebking 55 found that, in healthy subjects, neural activity in the DMN was negatively correlated with activity in the CEN (ie, as one increases, the other decreases).…”
Section: Considering An Extended Resting-state-based Model Of Soamentioning
confidence: 99%
“…There is evidence from several different experimental paradigms that ongoing resting-state activity in both the DMN and in the CEN can affect how internal/external The Sense of Agency and Schizophrenia stimuli are processed 31,35,55,[57][58][59] and that DMN activity is related to source attribution. 54,60,61 Specifically, stronger resting-state activity in the lateral regions of the CEN leads to an increased likelihood that mental contents will be construed as originating from the environment (non-self-related); whereas stronger activity in the DMN yields an increased focus on internal mental contents (self-related). 61,62 In healthy individuals, when processing internal/external stimuli there appears to be a negative correlation between the activity in the DMN and CEN; 35,55 ie, when activity in the DMN is stronger and the focus is on internal mental contents, there is a decrease in activity in the CEN, and vice versa.…”
Section: Soa Schizophrenia and The Resting Statementioning
confidence: 99%
“…Recently Northoff (2015) [4] proposed a general theory of the neurobiology of schizophrenia based on alterations in the spatiotemporal structure of resting-state activity. Recent studies on the functional resting-state alterations in schizophrenia suggest a fragmentation in the "stream of consciousness" in schizophrenic subjects, i.e.…”
mentioning
confidence: 99%